MRI Findings of La Crosse Virus Encephalitis in the Pediatric Population - Shariati, Farimah; Ganapathy, Shankar; Brown, Miraides; Upadhyayula, Shankar (Journal of the Pediatric Infectious Diseases Society, 2025)
This retrospective cohort study describes magnetic resonance imaging (MRI) findings in 56 patients with proven or probable La Crosse virus encephalitis. A review of the initial MRI images of patients during hospitalization revealed findings such as leptomeningeal enhancement, involvement of the thalamus, and the basal ganglia. Additionally, distinct findings of multiple punctate foci and frequent signal abnormality of the temporal lobe mimicking HSV were noted.